Racial inequities in the quality of surgical care among Medicare beneficiaries with localized prostate cancer. Issue 9 (13th February 2023) - Nyame, Yaw A.; Holt, Sarah K.; Etzioni, Ruth D.; Gore, John L.
Abstract: Background: US Black men are twice as likely to die from prostate cancer as men of other races. Lower quality care may contribute to this higher death rate. Methods: Sociodemographic and clinical data were obtained for men in Surveillance, Epidemiology, and End Results‐Medicare diagnosed with clinically localized prostate cancer (cT1‐4N0/xM0/x) and managed primarily by radical prostatectomy (2005–2015). Surgical volume was determined for facility and surgeon. Relationships between race, surgeon and/or facility volume, and characteristics of treating facility with survival (all‐cause and cancer‐specific) were assessed using multivariable Cox regression and competing risk analysis. Results: Black men represented 6.7% ( n  = 2123) of 31, 478 cohort. They were younger at diagnosis, had longer time from diagnosis to surgery, lower socioeconomic status, higher prostate‐specific antigen (PSA), and higher comorbid status compared with men of other races ( p  < .001). They were less likely to receive care from a surgeon or facility in the top volume percentile ( p  < .001); less likely to receive surgical care at a National Cancer Institute‐designated cancer center and more likely seen at a minority‐serving hospital; and less likely to travel ≥50 miles for surgical care. On multivariable analysis stratified by surgical volume, Black men receiving care from a surgeon or facility with lower volumes demonstrated increased risk of prostate cancer mortality (hazard ratio, 1.61; 95% confidence interval, 1.01–2.69) adjusting for age, clinical stage, PSA, and comorbidity index. Conclusions: Black Medicare beneficiaries with prostate cancer more commonly receive care from surgeons and facilities with lower volumes, likely affecting surgical quality and outcomes. Access to high‐quality prostate cancer care may reduce racial inequities in disease outcomes, even among insured men. Plain language summary: Black men are twice as likely to die of prostate cancer than other US men. Lower quality care may contribute to higher rates of prostate cancer death. We used surgical volume to evaluate the relationship between race and quality of care. Black Medicare beneficiaries with prostate cancer more commonly received care from surgeons and facilities with lower volumes, correlating with a higher risk of prostate cancer death and indicating scarce resources for care. Access to high‐quality prostate cancer care eases disparities in disease outcomes. Patient‐centered interventions that increase access to high‐quality care for Black men with prostate cancer are needed. Abstract : Lack of access to high quality care for Black men with prostate cancer may contribute to their substantially higher rate of death when compared with men of other races in the United States. Surgical volume—a surrogate for quality—and race are assessed in localized prostate cancer care.